UJI AKTIVITAS ANTI BAKTERI EKSTRAK KUNYIT TERHADAP PERTUMBUHAN Streptococcus mutans - Herlambang Prehananto; Ulfani H (Lembaga Pengembangan Kinerja Dosen, 2023)
The balance between bacteria and components of the mouth cavity must must be maintained in order to remain healthy and no damage such as dental caries. Streptococcus mutans as the main cause of bacteria dental caries, that functioned in the process of carbohydrate fermentation so as to produce acids that eventually cause tooth demineralization. One of the medicinal plants commonly used by the public is turmeric. Turmeric has active compounds can inhibit the growth of bacteria. Methods: Type of research True Experimental Laboratories with research design Post Test Only Control Group Design. This research used turmeric extract concentration 100%, 50%, 25%, 12,5%, 6,25%, 3,12%, 1,56%, 0,78%. The extract is created using maseration method, diluting series with dilution method, calculating MIC and MBC. Results: Test Saphiro Wilk and Levene test showed the value of p> 0.05 shows that the normal distribution of data. One Way Anova test results showed that p <0,05 showed that there was a significant difference overall. LSD test results there is a significant difference between the study groups. Conclusion: Turmeric extract (Curcuma domestica) has antibacterial power on growth of Streotococcus mutans bacteria at 3.12% MIC and 6.25% MBC.